2006
DOI: 10.1182/blood-2005-08-3451
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analysis of TEL/AML1-positive patients treated on Dana-Farber Cancer Institute Consortium Protocol 95-01

Abstract: In a retrospective analysis, we previously reported that children whose leukemia cells harbored the TEL/AML1 gene rearrangement have excellent outcomes. From 1996 to 2000, we conducted a prospective study to determine the incidence and outcomes of children with TEL/AML1-positive acute lymphoblastic leukemia (ALL). Children with newly diagnosed ALL were treated on DFCI ALL Consortium Protocol 95-01. Patients were risk stratified primarily by current National Cancer Institute (NCI)-Rome risk criteria. With a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
1
5

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 30 publications
7
64
1
5
Order By: Relevance
“…The strikingly similar outcomes of patients with TEL-AML1-positive ALL treated on the present study, on the DFCI 95-01 trial, 12 and at St. Jude 22 (EFS estimates of 86%, 89%, and 88%, respectively) indicate that different treatment strategies may result in equally good outcomes. Leukemic blasts from patients with TEL-AML1-positive ALL are sensitive to steroids, vincristine, and asparaginase in vitro, 23 and it has been suggested that the outstanding outcome of such patients on DFCI trials is related to the intensive use of asparaginase.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The strikingly similar outcomes of patients with TEL-AML1-positive ALL treated on the present study, on the DFCI 95-01 trial, 12 and at St. Jude 22 (EFS estimates of 86%, 89%, and 88%, respectively) indicate that different treatment strategies may result in equally good outcomes. Leukemic blasts from patients with TEL-AML1-positive ALL are sensitive to steroids, vincristine, and asparaginase in vitro, 23 and it has been suggested that the outstanding outcome of such patients on DFCI trials is related to the intensive use of asparaginase.…”
Section: Discussionsupporting
confidence: 54%
“…Leukemic blasts from patients with TEL-AML1-positive ALL are sensitive to steroids, vincristine, and asparaginase in vitro, 23 and it has been suggested that the outstanding outcome of such patients on DFCI trials is related to the intensive use of asparaginase. 12 However, the lack of intensive asparaginase administration in ALinC 16 or in the St. Jude trials suggests that the use of antimetabolite-based therapy or multiagent chemotherapy is also effective. Because of the excellent outcome of patients with TEL-AML1-positive ALL, very large randomized clinical trials will be required to determine the best possible therapy for these children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, TEL/AML1 accounts for about 20% of childhood ALL in most series worldwide. 23,24 In our series, a subgroup of 44 patients diagnosed since 1995 could be investigated for this chromosomal aberration, and only 1 case was positive. This might also be related to an age selection, given the propensity of DS patients to develop ALL at an older age, whereas TEL/AML1 is usually more frequent in younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 In pediatric B-cell precursor ALL, the most common structural genetic abnormality, present in 20-25% of the cases, is the t(12;21)(p13;q22), which results in the ETV6/ RUNX1 (also known as TEL/AML1) fusion gene. [2][3][4][5] ETV6/ RUNX1-positive ALLs are generally associated with a favorable outcome with an event free survival approaching 90%, 6 although late relapses have been noted by several groups. 7,8 Several lines of evidence suggest that ETV6/RUNX1 is not sufficient for leukemic transformation, such as detection of the gene fusion in Guthrie cards from patients who later developed ETV6/RUNX1-positive ALLs, 9 identical gene fusions in twins with concordant leukemia, 10 identification of the chimeric transcript in normal cord blood samples 11 and lack of leukemia in mouse models.…”
Section: Introductionmentioning
confidence: 99%